Working with nursing homes (VITAL, 2025)
From the Primary Health Care Line, health brigades were held in geriatric homes in Soacha and Guacamayas, where students and teachers attended to older adults through diagnoses, management plans and health education.
Keywords: Nursing homes; Primary Health Care; Health brigades